Differentiated Learning Based on Culturally Responsive Teaching (CRT) in Elementary Schools - Haryanti, Yuyun Dwi; Kumalasari, Eva Dwi; Saputra, Dudu Suhandi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The world of education is faced with global challenges that impact the diversity of each individual background based on interests, life experiences, perspectives, cultural knowledge, and language. The main objective of this study is to provide information from the literature on differentiated learning based on Culturally Responsive Teaching (CRT) in the latest Elementary Schools through a Systematic Literature Review (SLR). Overall, 1,099 articles with the keyword "Culturally Responsive Teaching (CRT)", 61 articles with the keyword "Differentiated learning based on Culturally Responsive Teaching (CRT)", and 10 articles with the keyword "Differentiated learning based on Culturally Responsive Teaching (CRT) in elementary schools" were published in Scopus during the period 2020-2024. This study provides the main tendencies that are relevant to the current global challenge conditions that elementary school teachers need to design differentiated learning based on Culturally Responsive Teaching (CRT) by considering the diversity of interests, life experiences, perspectives, cultural knowledge, and language of students in the classroom. The novelty of this research is centered on the analysis of differentiated learning and Culturally Responsive Teaching (CRT) applied in elementary schools. Teachers can design differentiated learning and Culturally Responsive Teaching (CRT) through self-identification, cultural understanding, collaboration, critical reflection, and transformative construction